Dramatization through Mise-En-Scene in Subuh Film (Miracle at Dawn) - Budi Dwi Arifianto; Adistia Ratna Salsabila (Jogjakarta Communication Conference (JCC), 2023)
At this time, the term indie film is familiar. Subuh (Miracle at Dawn) is one of the indie films that has received many awards both at home and abroad. This research discusses the mise en scene in building dramatic scenes in the Subuh film (Miracle at Dawn) by Achmad Rezi Fahlevie. Subuh (Miracle at Dawn) is a film with minimalist dialogue that packs a conflict of religious tolerance in one family. Every scene in the film makes the audience emotionally affected and feel involved in the story. A film with a strong story becomes meaningless without adequate cinematic achievements. Therefore, this research focuses on research in terms of cinematics focuses on the aspects of the scene and cinematography that build dramatic scenes. The purpose of this study is to analyze the dramatic elements in the Subuh film (Miracle at Dawn) and find out the role of mise en scene in building dramatic scenes in the film. This research uses a qualitative type of research using descriptive methods. The approximation used is the dramatic elements of Elizabeth Lutters, mise en scene, and cinematography. In this study, 4 scenes were built a dramatic scene in the Subuh film (Miracle at Dawn). Aspects such as setting, costumes, makeup, lighting, and players and movements can build dramatic scenes in the Subuh film (Miracle at Dawn).